Voice of Baceprot's Promotion of Feminism through the Music Industry - Faiz Mumtaz; Ni Lu Putu Ayu Pamethya Dharma Gurnita; Maharani Najla Ramaniya; Deasy Silvia Sari; R. Dudy Heryadi (Pusat Studi Gender Universitas Jember, 2025)
This study analyzes the promotion of feminism values by the Voice of Baceprot through their music. Feminism theory serves as a framework to examine how the Voice of Baceprot, as a women metal band, could work to promote gender inequality issues, not only in their home country but also in international scope. Using a qualitative approach and internet-based research, this research will explore the role of Voice of Baceprot in the context of promoting feminism values and breaking the unfavorable stigma that is associated with women in everyday life in society. The results of this research are expected to provide a deeper understanding of the Voice of Baceprot’s influence on the wider public, expressed through their songs that speak out about gender inequality and the need to rectify it.